MANAJEMEN PENDIDIKAN SENI TEATER DI KOMUNITAS SONGGOLANGIT CREATIVE SPACE SEBAGAI UPAYA MEMBANGUN RUANG KREATIF DAN STRATEGI REGENERASI - Niken Ayu Permata; Sabri, Indar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted in the bathara sandiwara division of the songgolangit community to answer the biggest obstacle of limited extracurricular theater arts activities in educational institutions. This research examines the management of theater arts education in the songgolangit creative space community as an effort to build a creative space consisting of several aspects, namely planning, organizing, mobilizing, controlling. Researchers used a qualitative approach method. The data collection techniques used are observation, interviews, and literacy studies, while in analyzing the data the steps taken first reduce the data, then proceed with the presentation of data and at the end draw conclusions. Researchers used triangulation of sources, techniques and time for data validity. Based on the results of the research in organizing theater arts education management, the songgolangit creative space community applies four management functions consisting of planning which is regulated in long and short term planning, realized with community programs that have been made, organizing with the preparation of community structures in organizing theater arts education, mobilizing which is carried out simultaneously with the implementation of art education and supervision carried out directly by the head of the community, this is done so that art education activities can run well and in accordance with the vision, mission, and goals of national education.